2022
DOI: 10.3390/antibiotics12010041
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Identification and Genetic Characterization of Antibiotic Resistant Escherichia coli from Frozen Chicken Meat Obtained from Supermarkets at Dhaka City in Bangladesh

Abstract: Antimicrobials have been used to improve animal welfare, food security, and food safety that promote the emergence, selection, and dissemination of antimicrobial-resistant (AMR) bacteria. In this study, 50 E. coli were isolated from frozen chicken meat samples in Dhaka city. Antibiotic sensitivity patterns were assessed through the disk diffusion method and finally screened for the presence of antimicrobial resistance genes (ARG) using the polymerase chain reaction (PCR). Among the 160 samples, the prevalence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 44 publications
2
3
0
Order By: Relevance
“…This study reported a significantly very high percentage of MDR (91.6%) in APEC isolates from different chicken types, and 73.3% of the isolates showed resistance against 7–10 different antimicrobials. Several national and international studies reported very high MDR isolates (80%–100%), which are similar to our findings from chicken [ 23 , 43 , 45 ], indicating that there is a high persistence of MDR organisms in our food chain. In alignment, previously detected high MDR-APEC prevalence (100%) in other food chain studies in migratory birds [ 65 ] are strong evidence of possible transmission of MDR organisms in our food chain system, which is perilous.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This study reported a significantly very high percentage of MDR (91.6%) in APEC isolates from different chicken types, and 73.3% of the isolates showed resistance against 7–10 different antimicrobials. Several national and international studies reported very high MDR isolates (80%–100%), which are similar to our findings from chicken [ 23 , 43 , 45 ], indicating that there is a high persistence of MDR organisms in our food chain. In alignment, previously detected high MDR-APEC prevalence (100%) in other food chain studies in migratory birds [ 65 ] are strong evidence of possible transmission of MDR organisms in our food chain system, which is perilous.…”
Section: Discussionsupporting
confidence: 90%
“…They were unable to achieve MIC values and were labor-intensive and time-consuming. These results may be more surprising [ 23 ] than broth microdilution. HiMedia, a manufacturer of low-potency disks, exhibited significant quality issues with 33% of readings being outside the normal range and surprising variations in inhibition zone sizes (4–9 mm) for disks contained in the same vial [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Shigella spp. samples in Dhaka are consistent with previous research conducted in other countries(Angkititrakul et al, 2013;Bodhidatta et al, 2013;Hossain et al, 2022;Paudyal et al, 2017). There are very few data on such studies in Bangladesh, though some studies were performed on chicken and frozen meat(Uddin et al, 2019).…”
supporting
confidence: 89%
“…Focusing on the microbiological aspect of food, the presence of E. coli may indicate poor and unhygienic food handling and fecal contamination. Therefore, the detection of E. coli and its virulence properties is an important consideration while assessing the microbiological quality of food (Hossain et al., 2023 ; Sherikar & Bachhi, 2011 ). Furthermore, the presence of pathogens, including E. coli , in food could be attributable to cross‐contamination, temperature abuse, and unhygienic food handling, which are important aspects of food safety (Todd et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%